The Portrayal of Children's Activities in Television Commercials: A Content Analysis - Peterson, Robin T. (Journal of business ethics, 1998)
This study used a content analysis of television commercials to analyze the depiction of pre-teens and teens. It uncovered evidence that children are not often depicted in scholastic roles in the commercials. Further, it found that when children are shown in these roles, the portrayal is frequently not favorable. Various implications of the findings and recommendations to advertisers are set forth. Foremost among these is that television commercials do not seem to be assisting in forming positive attitudes toward scholastic activities. More favorable depictions could improve the image of scholarly activity and assist in reducing criticisms of television advertising Advertiser's who seek action prescriptions as to how they might ethically depict children can benefit from applications of the study results to their creative efforts.